Perbandingan Penyelesaian SPL dengan Metode Eliminasi Gauss Menggunakan Aplikasi Berbasis Windows dan Android - Novia Rista Ramadhani; Anysa Puspitasari; Nazwa Afrilia Soliha; Ari Wibowo (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This study aims to compare the solution of systems of linear equations (SLE) using the Gaussian elimination method through Windows and Android-based applications. This study is a comparative study with a quantitative descriptive approach focusing on the analysis of calculation results and the efficiency of software usage in the context of numerical analysis. Data were obtained from two SLE problem scenarios involving fractional and decimal coefficients, which were then solved using several applications, namely Maple, Microsoft Excel, and the Gauss-Elim calculator. The analysis was conducted based on aspects of accuracy, efficiency, possibility of errors, and ease of use. The results show that Windows and Android-based applications produce the same solutions despite following different solution procedures. Maple demonstrates a high level of accuracy with a systematic and structured solution process. Microsoft Excel requires greater precision because most procedures are carried out manually through elementary row operations. Meanwhile, the Gauss-Elim calculator is the most practical and efficient application because it can display solutions automatically in a short time. Therefore, each application has its own advantages and limitations in supporting SLE solutions using the Gaussian elimination method.